2021
DOI: 10.1038/s41467-021-26742-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal prediction of COVID-19 cases using inter- and intra-county proxies of human interactions

Abstract: Measurements of human interaction through proxies such as social connectedness or movement patterns have proved useful for predictive modeling of COVID-19, which is a challenging task, especially at high spatial resolutions. In this study, we develop a Spatiotemporal autoregressive model to predict county-level new cases of COVID-19 in the coterminous US using spatiotemporal lags of infection rates, human interactions, human mobility, and socioeconomic composition of counties as predictive features. We capture… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 55 publications
(47 reference statements)
0
18
0
1
Order By: Relevance
“…Together, these features help capture the heterogeneous spatial spread of COVID-19, both intra- and inter-county, for a given week [ 93 ]. In order for our model to learn the spatiotemporal spread, we create temporal series of the weekly averages of each of these variables.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these features help capture the heterogeneous spatial spread of COVID-19, both intra- and inter-county, for a given week [ 93 ]. In order for our model to learn the spatiotemporal spread, we create temporal series of the weekly averages of each of these variables.…”
Section: Datamentioning
confidence: 99%
“…SCI is a static index produced annually; however, as SPC is weighted by the weekly COVID-19 incidence rate, SPC is a dynamic measure of proximity to cases. Together, these features help capture the heterogeneous spatial spread of COVID-19, both intra-and inter-county, for a given week [93]. In order for our model to learn the spatiotemporal spread, we create temporal series of the weekly averages of each of these variables.…”
Section: Facebook-derived Spatial Featuresmentioning
confidence: 99%
“…95% "zero" 90% "zero" 80% "zero" 70% "zero" 60% "zero" 50% "zero" accuracy, especially for counties with very small/zero sample sizes. Some studies (Khan et al, 2018;Gibbs et al, 2020;Oleson et al, 2008;Vahedi et al, 2021) suggested incorporating the spatial random effect by borrowing strength from space can improve model fit and estimate accuracy. The topic is slightly out of the scope of this study, we may explore the spatial random effect in the BBZ and other BHR models in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…Space–time models also need to incorporate the spatial diffusion or spillover related to behaviours such as commuting [ 18 , 19 ]. It is also especially useful in policy terms to be able to extrapolate the infectious disease evolution beyond the observation span, as illustrated in some studies of the COVID epidemic [ 20 , 21 , 22 , 23 ].…”
Section: Relevant Literaturementioning
confidence: 99%